The marine chert from Las Lezas (Biel, Zaragoza) within the lithic raw materials management in the Arba de Biel sites (Journal of Lithic Studies, 2016)
The upper Arba de Biel Basin hosts an interesting archaeological ensemble composed by five sites that were repeatedly occupied by human groups from the Upper Magdalenian until the Chalcolithic (between ca. 15,000 and 4,500 years calBP). Our research group has worked at the area since 1999, revealing one of the most coherent prehistoric ensembles of the Ebro Basin. Accurately framed thanks to thirty-five radiocarbon dates, it offers great study possibilities that are the basis for several PhDs: anthracology, faunal remains or lithic raw materials are already offering copious data that help to reconstruct the prehistoric life in that secluded area.This work presents the first results of the petrographic study of the local chert (Las Lezas), which was the main lithic raw material exploited by the human groups that frequented the area. This paper is also the first one that characterizes in petrological terms this chert outcrop. The different contribution along time of this local variety and other exogenous cherts like Monegros and Evaporitic of Ebro to the lithic assemblages from the five analysed sites are exposed in the final section of our work. There is a notable shift in lithic raw materials management from Magdalenian to Neolithic times: at first, local chert is predominant, with special tools knapped in good-quality Monegros chert. In Neolithic times, Las Lezas chert is barely employed and exogenous Evaporitic white chert is especially chosen to knap blades that eventually are used to obtain double-bevel retouched geometric microliths.